Uji Kinerja Mesin Pengiris dan Pemarut Ganyong (MPPG) Tep-02 - Yusuf, Asep; Sinaga, Lambok; Sugandi, Wahyu K. (Proceedings Series on Physical & Formal Sciences, 2021)
Canna (Canna edulis Kerr.) is a type of tuber plant with a fairly high starch content to be used as food. The use of canna is generally processed first into flour. The initial process of flouring canna is done in two ways; the canna plants are sliced and grated. The Department of Agricultural and Biosystem Engineering, Faculty of Agricultural Industrial Technology, University of Padjadjaran, designed the TEP-1902 Canna Slicing and Shredding Machine (MPPG). However, the performance of this machine was not yet known, so testing was needed to determine its performance. The research method used was an experimental method that was analyzed descriptively by measuring, observing, calculating, analyzing, testing, and evaluating the TEP-1902 Canna Slicing and Shredding Machine (MPPG). The results of the performance test of this machine showed that the machine's performance was good, with the following parameters: the actual capacity of the slicing unit and grating unit was 40.95 kg/hour and 182.98 kg/hour, respectively, efficiency was 92.61% slicing and 97.60% grater, the yields were 98.75% slicing and 96.50% grating, respectively, the average thickness of the slices was 2.13 mm, and the uniformity of slice thickness was 65.51%.